PERKAWINAN BELEKET MENURUT ADAT REJANG DI REJANG LEBONG DITINJAU DARI HUKUM ISLAM - Majana, Sanuri (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
The custom is the code  of conduct in life that includes real aspect that has  been set as custom wedding, this research is the  study  of shapes of marriage beleket (mating  honest) Rejang  Rejang  Lebong  in customs. In this study researchers using this type of research libraries  (Library Research). I.e. using techniques of data  collection undertaken by way of reading  and  reviewing  some literature  or books  as well as legislation  relating to problems in thorough, as for activities conducted in the analysis  of the data,  namely:  1. Looking for books  to find understanding and  laws regulating marriage beleket (mating  honest) custom Rejang. 2. Choose  the verses  of Qur’an and  Hadith about  marriage as well as books  of Fiqh related. 3. create a systematic verses  of Qur’an and  Hadith  and  Fiqh books.  4. The Data obtained in the analysis  of inductive  qualitative  basis.The results  of this research indicate that: 1. marriage beleket/honest is a form of marriage in the family requires the Rejang, bid pay money  to be honest or to the girl leket and in mating beleket/jujurnya big money  this honest and  much more  cakkercik (besides money). honest marriage is a form  of marriage eksogami, children  then  enter  klen or bloodlines father, because marriage is a marriage that ensured beleket bloodlines patrlineal.2. in the the purpose of Marriage beleket is equal  to marriage in accordance with the concept of marriage in Islam i.e. marriage must be Sekufu described in the Qur’an in Sura An Nur, verse 26 An Nur, verse 3 and Al Hujurat verse 13. In the procession of honest marriage/marriage beleket Rejang Rejang Lebong in customs were in accordance with the marriage in Islam and  not against  syari ‘, but with a result of beleket in the form of marriage gitie tikea (replace the mat)  should be abandoned because it is in the form of the larger tikea gitie mafsadahnya from on maslahah obtained, according to the word of God Saw in Qur’an Sura Al-Baqarah verse and Hadith the Messenger of Almighty, 234. In fostering  domestic life forms indigenous beleket Rejang marriage greater  mafsadahnya of maslahah in accordance with the Quran,  Hadith, Fiqh rules, so that the form of the marriage custom of the Rejang beleket called ‘urf fasid is incompatible with the Islamic Sharia’. The law it is al muharram li Dzatihi